2016
DOI: 10.1038/cddis.2016.164
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress in bone marrow-derived cells prevents acute cardiac inflammation and injury in response to angiotensin II

Abstract: Inflammation plays an important role in hypertensive cardiac injury. The endoplasmic reticulum (ER) stress pathway is involved in the inflammatory response. However, the role of ER stress in elevated angiotensin II (Ang II)-induced cardiac injury remains unclear. In this study, we investigated the role of ER stress in Ang II-induced hypertensive cardiac injury. Transcriptome analysis and quantitative real-time PCR showed that Ang II infusion in mice increased ER stress-related genes expression in the heart. C/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…CaMKIIδ-mediated inflammatory gene expression accompanied by macrophage accumulation both occur within 1 day of Ang II treatment, a time point shown here and in the literature to not be associated with death of cardiomyocytes (60). Thus, while CaMKIIδ has been implicated in processes that elicit various forms of cardiomyocyte cell death (61)(62)(63)(64)(65), the modest level of CaMKIIδ activation observed at early times of Ang II infusion serves to elicit inflammatory responses through a rapidly activated transcriptional pathway in cardiomyocytes, rather than through factors released by dying cells.…”
Section: Discussionsupporting
confidence: 63%
“…CaMKIIδ-mediated inflammatory gene expression accompanied by macrophage accumulation both occur within 1 day of Ang II treatment, a time point shown here and in the literature to not be associated with death of cardiomyocytes (60). Thus, while CaMKIIδ has been implicated in processes that elicit various forms of cardiomyocyte cell death (61)(62)(63)(64)(65), the modest level of CaMKIIδ activation observed at early times of Ang II infusion serves to elicit inflammatory responses through a rapidly activated transcriptional pathway in cardiomyocytes, rather than through factors released by dying cells.…”
Section: Discussionsupporting
confidence: 63%
“…4,51,52 However, the precise inflammatory pathways which are induced by Ang II are not well established yet in beta cells as well in other tissues. 53,54 Our study and others have demonstrated that activation of RAAS could contribute to inflammation. 21 Furthermore, increased Chop expression, an ER stress marker, induced inflammation through the NFkB pathway.…”
Section: Dovepressmentioning
confidence: 64%
“…Thus inflammation is a key mediator of AngII-induced beta cell dysfunction (11). A role for ER stress in AngII-mediated inflammation has recently been shown in other cell types/tissues (41)(42)(43), yet the mechanism by which this occurs had not been fully explored.…”
Section: Discussionmentioning
confidence: 99%